2022
DOI: 10.1186/s12877-022-03655-7
|View full text |Cite|
|
Sign up to set email alerts
|

Association between low back pain and functional disability in the elderly people: a 4-year longitudinal study after the great East Japan earthquake

Abstract: Background Functional disability is a major health issue in an aging population. Low back pain (LBP) is a common health concern that can lead to functional disability in the elderly; nonetheless, their association has not yet been clarified. This study aimed to examine the association between LBP and functional disability in the elderly, with a focus on its dose-dependent effects. Methods This study used the 4-year longitudinal data of people livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
4
0
1
Order By: Relevance
“…While after cupping therapy, reduced pain severity was linked to less disability levels (table 6). This finding is in a harmony with other studies done in Egypt by Abd El Moniem et al (2019) (10) , in Thailand by Sakulsriprasert et al (2021) (39) , and in Japan by Yabe et al (2022) (40) .…”
Section: Table (1):-distribution Of the Cupping And Control Groups Ac...supporting
confidence: 91%
“…While after cupping therapy, reduced pain severity was linked to less disability levels (table 6). This finding is in a harmony with other studies done in Egypt by Abd El Moniem et al (2019) (10) , in Thailand by Sakulsriprasert et al (2021) (39) , and in Japan by Yabe et al (2022) (40) .…”
Section: Table (1):-distribution Of the Cupping And Control Groups Ac...supporting
confidence: 91%
“…Another explanation is that disability attributed to BP varies substantially across countries and it is influenced by social norms, local health approaches, and legislation [ 3 ]. A Japanese study demonstrated that BP is associated with functional disability, and such association is observed to be stronger in a dose-dependent manner, which includes the intensity, frequency, and duration of BP [ 47 ]. In the present study the sample was considered as a whole, which may have masked possible effects in subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that disability attributed to BP varies substantially across countries and it is in uenced by social norms, local health approaches, and legislation [3]. A Japanese study demonstrated that BP is associated with functional disability, and such association is observed to be stronger in a dosedependent manner, which includes the intensity, frequency, and duration of BP [44]. In the present study the sample was considered as a whole, which may have masked possible effects in subgroups.…”
Section: Hrqol and Disabilitymentioning
confidence: 99%